Exploring Linguistic Anti-Feminism in Selected Short Stories of Danyial Mueenuddin (Journal of Asian Development Studies, 2025)
This study investigates the relationship between language and gender in Danyial Mueenuddin's selected short stories from his collection, In Other Rooms, Other Wonders. Employing Sara Mills' (2008) model of overt and indirect anti-feminism, a qualitative textual analysis was conducted on four stories: "Saleema," "In Other Rooms, Other Wonders," "About a Burning Girl," and "Provide, Provide." The findings reveal persistent instances of linguistic anti-feminism. Overt anti-feminism manifests through derivational nouns (e.g., sweepress, shepherdess) and insulting swear words (e.g., slut), which explicitly demean female characters. Indirect anti-feminism is conveyed through metaphors (e.g., plaything, black mangoes) and irony, which subtly reinforce gender stereotypes and objectify women. The analysis concludes that Mueenuddin's linguistic choices, while reflective of his patriarchal settings, perpetuate gender inequalities by marginalising and belittling women. This research underscores the significance of critical language awareness in challenging and transforming ingrained societal attitudes toward gender in literature.